Synthesis, pharmacology and molecular docking on multifunctional tacrine-ferulic acid hybrids as cholinesterase inhibitors against Alzheimer's disease. (1st January 2018) - Zhu, Jie; Yang, Hongyu; Chen, Yao; Lin, Hongzhi; Li, Qi; Mo, Jun; Bian, Yaoyao; Pei, Yuqiong; Sun, Haopeng
Abstract: The cholinergic hypothesis has long been a "polar star" in drug discovery for Alzheimer's disease (AD), resulting in many small molecules and biological drug candidates. Most of the drugs marketed for AD are cholinergic. Herein, we report our efforts in the discovery of cholinesterases inhibitors (ChEIs) as multi-target-directed ligands. A series of tacrine-ferulic acid hybrids have been designed and synthesised. All these compounds showed potent acetyl-(AChE) and butyryl cholinesterase(BuChE) inhibition. Among them, the optimal compound10g, was the most potent inhibitor against AChE (electrophorus electricus (eeAChE) half maximal inhibitory concentration (IC50 ) = 37.02 nM), it was also a strong inhibitor against BuChE (equine serum (eqBuChE) IC50  = 101.40 nM). Besides, it inhibited amyloid β-protein self-aggregation by 65.49% at 25 μM. In subsequent in vivo scopolamine-induced AD models, compound10g obviously ameliorated the cognition impairment and showed preliminary safety in hepatotoxicity evaluation. These data suggest compound10g as a promising multifunctional agent in the drug discovery process against AD. Graphical Abstract: